Association between Helicobacter pylori infection & atrophic gastritis - AL-Hadithi, Hayfaa S. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Helicobacter pylori (H. pylori) infection is associated with gastritis and may induce atrophic gastritis have specific circulating immunoglobulin G (IgG) antibodies.Aim of the study: To confirm the correlation between Helicobacter pylori infection and gastric atrophy.Patient and Method: A study was conducted in the period between December 2005 and March 2006 on 25 patients with atrophic gastritis attending Gastroenterology and Hepatology Teaching Hospital in Baghdad, and 25 healthy volunteers who agreed to donate blood. Sera were tested for H. pylori IgG Ab by ELISA test.Results and Conclusions: detection of H. pylori IgG Ab were applied to each individual, showed that (92 %) of patients with atrophic gastritis had positive H. pylori IgG Ab were as only 4 (16 %) of normal healthy individuals had positive H. pylori IgG Ab.